Financial Performance Evaluation Using Various Economic Value Added Measures in the Consumer Sector of the Iraq Stock Exchange - Abdulsalam al-bunajim, Osama; Ghobadi, Sara; Mohamad Hussein, Abdulrazzaq; Sharifi Renani, Hossein (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to evaluate the impact of three contemporary economic performance metrics on the financial performance of consumer sector companies listed on the Iraq Stock Exchange. Methodology: A dynamic panel data approach using the Arellano and Bond method was employed to analyze data from 16 companies over 7 years. Variables including EVA, REVA, ENEVA, Return on Investment (ROI), financial ratios, sales growth rate, financial risk, market indicators, and advertising expenditures were evaluated for their influence on return on assets (ROA). Findings: All three EVA metrics showed significant positive effects on financial performance, with REVA identified as the most effective measure. ROI, financial ratios, sales growth rate, and advertising expenditures also positively influenced ROA, while financial risk negatively impacted performance. The Sargan and serial correlation tests confirmed the validity of the instruments and model. Conclusion: The results emphasize the utility of EVA-based metrics, particularly REVA, as robust tools for financial performance evaluation and improvement in the consumer sector. These metrics provide a comprehensive perspective by incorporating capital costs, enabling firms to identify improvement opportunities and enhance long-term shareholder value.